Rationale and Design Considerations for a Semantic Mediator in Health Information Systems - Degoulet, P.; Sauquet, D.; Jaulent, M.-C.; Zapletal, E.; Lavril, M. (Methods of Information in Medicine, 1998)
Rapid development of community health information networks raises the issue of semantic interoperability between distributed and heterogeneous systems. Indeed, operational health information systems originate from heterogeneous teams of independent developers and have to cooperate in order to exchange data and services. A good cooperation is based on a good understanding of the messages exchanged between the systems. The main issue of semantic interoperability is to ensure that the exchange is not only possible but also meaningful. The main objective of this paper is to analyze semantic interoperability from a software engineering point of view. It describes the principles for the design of a semantic mediator (SM) in the framework of a distributed object manager (DOM). The mediator is itself a component that should allow the exchange of messages independently of languages and platforms. The functional architecture of such a SM is detailed. These principles have been partly applied in the context of the HEllOS object-oriented software engineering environment. The resulting service components are presented with their current state of achievement.
Keywords: Semantic Interoperability; Data Exchange; Data Messaging; Semantic Mediator